Pelvic lymphadenectomy as a component of interval cytoreduction for ovarian cancer: is there a benefit? A pilot study - Kumar, D. Suresh; Noushad, S. Navin; Viswanathan, M. P. (International Journal of Research in Medical Sciences, 2017)
Background: Management strategy in ovarian cancer includes a combination of cytoreductive surgery and chemotherapy. Interval cytoreductive surgery has been shown to be oncologically non-inferior to primary cytoreduction with the additional benefit of reduced morbidity. Lymphadenectomy as a component of cytoreductive surgery has been controversial with an unproven therapeutic benefit. Methods: Records of patients with a histological diagnosis of ovarian cancer and treated with interval cytoreduction were evaluated. Disease related, pathological and treatment data collected for analysis. Results: The study included 32 patients with a mean age of 56 years (41-76). Serous papillary tumors (42%) were the predominate histology and the majority were in stage III disease (84%). Optimal cytoreduction was achieved in 93%. The mean nodal harvest was 9.8 nodes with left pelvic dissection yielding slightly more nodes than the right (4.5 vs 5.2). Nodal positivity was observed in just one patient (3%). A total of 314 were nodes examined with only 2 (0.6%) yielding persistent disease. The nodal positivity yield tested as a categorical variable by the binomial test returned P=0.0001. Conclusions: It is possible to omit pelvic nodal dissection during interval cytoreduction in otherwise optimally cytoreduced patients particularly when imaging and intraoperative assessment are not suggestive of pelvic nodal metastasis.